The course of fatigue and its correlates in colorectal cancer survivors: a prospective cohort study of the PROFILES registry - Husson, Olga (Support Care Cancer, 2015)
PURPOSE: Colorectal cancer (CRC) survivors who remain fatigued during long-term follow-up are at risk for worse health outcomes and need relevant interventions most. The aim of this study is to prospectively assess cancer-related fatigue (CRF) and four categories of CRF correlates (clinical characteristics, demographic characteristics, behavior/well-being, functional status). METHODS: CRC survivors diagnosed between 2000 and 2009, as registered in the population-based Eindhoven Cancer Registry, completed the Fatigue Assessment Scale at three annual time points. Linear mixed models were used to assess the course of CRF and identify its correlates. RESULTS: CRF levels were relatively stable over time. Being female, young (≤65 years of age), and single; having a low educational level; treatment with chemotherapy; and having one or more comorbid conditions were associated with higher CRF scores. Years since diagnosis, radiotherapy, and disease stage were not related to CRF over time. Significant between- and within-subject effects were found for all well-being factors (social, emotional, and cognitive functioning, and global quality of life), symptoms (anxiety, depression, pain, and insomnia), and functional status (physical and role functioning, physical activity levels) in relation to CRF. The differences in CRF levels could, for a large part, be attributed to differences in behavior/well-being (59 %), functional status (37 %), and, to a lesser extent, to sociodemographic (4 %) and clinical characteristics (8 %). CONCLUSION: This study showed that sociodemographic and clinical factors were associated with CRF levels over time among CRC survivors; however, behavior/well-being and functional status explained a larger part of the variance in levels of CRF.